2006
DOI: 10.1002/jctb.1570
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glucose:xylose ratio on xylose reductase and xylitol dehydrogenase activities from Candida guilliermondii in sugarcane bagasse hydrolysate

Abstract: The influence of glucose on xylose reductase (XR) and xylitol dehydrogenase (XDH) enzyme activity was evaluated from sugarcane bagasse hydrolysate fermentations with different glucose:xylose ratios (1:25, 1:12, 1:5 and 1:2.5) by employing an inoculum of Candida guilliermondii grown in media containing glucose, a mixture of glucose and xylose, or only xylose as carbon sources. According to the results, the glucose:xylose ratio affected positively this bioconversion and a correlation was not observed between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
1
11

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 31 publications
2
15
1
11
Order By: Relevance
“…This reduction in xylitol concentration was also observed during the cultivation of C. guilliermondii in synthetic medium (Felipe et al 1995) and in sugarcane bagasse hydrolysate Sene et al 1998), and also during the cultivation of C. tropicalis in synthetic medium (Walther et al 2001). Recently, experiments performed in our laboratories revealed that xylitol was utilized as a carbon source by C. guilliermondii for cell growth (Silva and Felipe 2006). Formation of glycerol and ethanol by-products during this metabolism was also improved by the increase in glucose:xylose ratio.…”
Section: Discussionsupporting
confidence: 57%
“…This reduction in xylitol concentration was also observed during the cultivation of C. guilliermondii in synthetic medium (Felipe et al 1995) and in sugarcane bagasse hydrolysate Sene et al 1998), and also during the cultivation of C. tropicalis in synthetic medium (Walther et al 2001). Recently, experiments performed in our laboratories revealed that xylitol was utilized as a carbon source by C. guilliermondii for cell growth (Silva and Felipe 2006). Formation of glycerol and ethanol by-products during this metabolism was also improved by the increase in glucose:xylose ratio.…”
Section: Discussionsupporting
confidence: 57%
“…In addition, studies have shown that xylitol prevents osteoporosis, haemolytic anaemia and acute otitis (Mussatto and Roberto 2002). Xylitol can be produced by the chemical reduction of D-xylose derived mainly from lignocellulose biomass hydrolysates (Chen et al 2010;da Silva and Chandel 2012;Mohamad et al 2015). However, the requirement for several purification steps to separate xylitol from other polyols and sugars during the chemical process increases the production cost.…”
Section: Introductionmentioning
confidence: 98%
“…-dependent xylitol dehydrogenase (XDH) (da Silva et al 1996). D-xylulose is then phosphorylated by xylulokinase (XK) to produce Dxylulose-5-phosphate, which can be converted into pyruvate via a connection between the pentose phosphate and the glycolytic pathways (Winkelhausen and Kuzmanova 1998;da Silva and Felipe 2006). The redox equilibrium between the reactions catalysed by XR and XDH favours xylitol production (Winkelhausen and Kuzmanova 1998).…”
Section: Introductionmentioning
confidence: 99%
“…This last sugar was added to the medium used to grow the inoculum in order to induce the expression of enzymes necessary for xylose metabolism, like xylose reductase and xylitol dehydrogenase (16). It was expected that the growth of the cells in an inducing medium would speed up the xylitol bioproduction in the hydrolysate-based medium, since the xylose-to-xylitol bioconversion is influenced by the type and ratio of sugars present in fermentation media (18).…”
mentioning
confidence: 99%